Exercise tolls the bell for key mediators of low-grade inflammation in dysmetabolic conditions. (December 2021) - Della Guardia, Lucio; Codella, Roberto
Abstract: Metabolic conditions share a common low-grade inflammatory milieu, which represents a key-factor for their ignition and maintenance. Exercise is instrumental for warranting systemic cardio-metabolic balance, owing to its regulatory effect on inflammation. This review explores the effect of physical activity in the modulation of sub-inflammatory framework characterizing dysmetabolic conditions. Regular exercise suppresses plasma levels of TNFα, IL-1β, FFAs and MCP-1, in dysmetabolic subjects. In addition, a single session of training increases the anti-inflammatory IL-10, IL-1 receptor antagonist (IL-1ra), and muscle-derived IL-6, mitigating low-grade inflammation. Resting IL-6 levels are decreased in trained-dysmetabolic subjects, compared to sedentary. On the other hand, the acute release of muscle-IL-6, after exercise, seems to exert a regulatory effect on the metabolic and inflammatory balance. In fact, muscle-released IL-6 is presumably implicated in fat loss and boosts plasma levels of IL-10 and IL-1ra. The improvement of adipose tissue functionality, following regular exercise, is also critical for the mitigation of sub-inflammation. This effect is likely mediated by muscle-released IL-15 and IL-6 and partly relies on the brown-shifting of white adipocytes, induced by exercise. In obese-dysmetabolic subjects, moderate training is shown to restore gut-microbiota health, and this mitigates the translocation of bacterial-LPS into bloodstream. Finally, regular exercise can lower plasma advanced glycated endproducts. The articulated physiology of circulating mediators and the modulating effect of the pathophysiological background, render the comprehension of the exercise-regulatory effect on sub-inflammation a key issue, in dysmetabolism. Graphical Abstract: ga1 Highlights: In inactive subjects, adipose tissue-muscle crosstalk increases low-grade inflammation. Exercise-induced cytokines have a metabolic/inflammatory rebalancing effect. Exercise ameliorates low-grade inflammation by improving adipose tissue functionality. Regular exercise lowers plasma lipopolysaccharide concentration by improving gut health. Training decreases mediators of low-grade inflammation in healthy and dysmetabolic subjects.